2020
DOI: 10.3390/md18010052
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment with Laminarin Protects Hippocampal CA1 Pyramidal Neurons and Attenuates Reactive Gliosis Following Transient Forebrain Ischemia in Gerbils

Abstract: Transient brain ischemia triggers selective neuronal death/loss, especially in vulnerable regions of the brain including the hippocampus. Laminarin, a polysaccharide originating from brown seaweed, has various pharmaceutical properties including an antioxidant function. To the best of our knowledge, few studies have been conducted on the protective effects of laminarin against ischemic injury induced by ischemic insults. In this study, we histopathologically investigated the neuroprotective effects of laminari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…On the other hand, as a result of ischemic damage to the prefrontal cortex, the levels of GFAP increased, which may indicate the development of astrogliosis. Previously, remote cortical damage in the sensorimotor or prefrontal region has been shown to cause the proliferation of reactive astrocytes (Sandhir et al, 2008;Chin et al, 2013;Lee et al, 2020). Our results are also consistent with data from Gao and coauthors, who showed an increase in GFAP + cells in the granule cell layer and hilus zone (Gao et al, 2009) in a similar mouse line during TBI modeling.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, as a result of ischemic damage to the prefrontal cortex, the levels of GFAP increased, which may indicate the development of astrogliosis. Previously, remote cortical damage in the sensorimotor or prefrontal region has been shown to cause the proliferation of reactive astrocytes (Sandhir et al, 2008;Chin et al, 2013;Lee et al, 2020). Our results are also consistent with data from Gao and coauthors, who showed an increase in GFAP + cells in the granule cell layer and hilus zone (Gao et al, 2009) in a similar mouse line during TBI modeling.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the case of inflammation, Neyrinck et al (2007) showed that laminarin protected against LPS-induced hepatotoxicity in rats via a decrease in the serum monocyte number, nitrite, and TNFα. Additionally, we recently reported that laminarin pretreatment strongly attenuated activations of astrocytes and microglia in the hippocampal CA1 after brain IR in gerbils [28]. Thus, together with our and other previous studies, our current findings potentially suggest that alleviation of oxidative stress and neuroinflammation in the ischemic hippocampal CA1 of aged gerbils by pretreatment with laminarin contributes to neuroprotection against IR injury.…”
Section: Discussionsupporting
confidence: 87%
“…Pretreated fucoidan, for example, significantly reduces cerebral infarction size following transient focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO)in adult rats [25] and protects pyramidal neurons in the hippocampal CA1 from IR injury in an adult gerbil model of transient global forebrain ischemia [27]. Furthermore, we recently reported that laminarin pretreatment had a strong neuroprotection in the hippocampal CA1 against IR injury in an adult gerbil model of transient global forebrain ischemia [28]. However, the above-mentioned studies were done in adult animal models; these studies have a limitation in not addressing ischemic insults in the aged population with a higher risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations